I know what you want to know : The impact of interviewees´ ability to identify criteria on interview performance and construct-related validity. - Melchers, Klaus G.; Klehe, Ute-Christine; Richter Gerald M.; Kleinmann, Martin; Koenig, Cornelius J.; Lievens, Filip; Justus Liebig University Giessen (My University, 2009)
The current study tested whether candidates´ ability to identify the targeted interview dimensions fosters their interview success as well as the interviews´ convergent and discriminant validity. Ninety-two interviewees participated in a simulated structured interview developed to measure three different dimensions. In line with the hypotheses, interviewees who were more proficient at identifying the targeted dimensions received better evaluations. Furthermore, interviewees´ ability to identify these evaluation criteria accounted for substantial variance in predicting their performance even after controlling for cognitive ability. Finally, the interviewer ratings showed poor discriminant and convergent validity. However, we found some support for the hypothesis that the quality of the interviewer ratings improves when one only considers ratings from questions for which interviewees had correctly identified the intended dimensions.
Keywords: structured interview; targeted interview dimensions; identification of evaluation criteria; interview performance; ddc:150